Capitalizing Trees for Carbon Sequestration as a Co-Benefit of Biophilic Urbanism: Capitalizing Trees for Carbon Sequestration as a Co-Benefit of Biophilic Urbanism - Namood-e-Sahar; Kishwar, Farzana; Tahir, Arifa; Ullah, Muhammad Aboid (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
Biophilic urbanism as an emerging paradigm in the design field has initiated various patterns of naturebased mutation. One of the most associated environmental benefits of this amalgamation of nature in urban design is carbon sequestration [CS]. The main focus of this research was to quantify the potential of trees to act as carbon reservoirs. It was investigated by assessing the roles of several tree parameters, such as diameter at breast height [DBH], height, biomass, and age in CS. A comparison of native and exotic trees was also done for this. In a field survey at Jilani Park, Lahore, 16 different families of trees (N = 115) were measured through a non-destructive method and CS was calculated. The results revealed that sample trees sequestered 588452.9 kg of carbon with an annual rate of 19998.92 kg and Combretaceae (M = 11813.65, SD = 6492.38) and Moraceae (M = 9909.93, SD = 12695.26) were the dominant families in doing so. The Pearson’s correlation and linear regression analyses indicated that biomass and DBH have a significant positive relationship with CS, r = 0.100, R2 = 0.99, and r = 0.943, R2 = 0.89, respectively. The independent-sample t-test revealed a significant difference in CS capacity between native and exotic trees, with t (67.626) = 3.016, p =.004, and the greater biomass and DBH of native trees were the distinguishable factors. To conclude, trees are the most efficient source of carbon attenuation in the urban environment, and native species have an advantage in this process. This study will inspire new endeavours in research related to the benefits of biophilic cities.